An evaluation of green manufacturing technologies based on research databases - Ahn, Sung-Hoon (International Journal of Precision Engineering and Manufacturing-Green Technology, 1(1), 2014)
The International Journal of Precision Engineering and Manufacturing-Green Technology (IJPEM-GT) was inaugurated in order to foster knowledge sharing and collaboration of researchers in the field of “green manufacturing.” While emerging technologies can be evaluated by business points of view such as Hype Cycle of Gartner, in this paper, journals and research areas in green manufacturing were evaluated by using research databases such as Web of Science and Journal Citation Report. Using impact factor and the number of published papers as key parameters, journals in subjects of Engineering-Mechanical, Engineering-Manufacturing, Engineering-Environmental, and Energy and Fuels were compared. From the point of researchers, the H-Index and the number of published papers were evaluated for journals and technologies in green manufacturing. The H-Index of journals or research areas was proportional to logarithm of the number of papers, and linear trend lines were observed from the data. The journals in green technology show higher gradient in the trend line compared with the journals in manufacturing and environmental areas. In addition, a Four Stage Model (early-emerging-developed-saturated stages) of technology development was proposed.